The Influence of the Tibetan Plateau Monsoon on Summer Precipitation in Central Asia - Zhang, Shaobo; Meng, Lixia; Zhao, Yong; Yang, Xianyu; Huang, Anning (Frontiers in Earth Science, 2022)
As a unique climate phenomenon induced by the Tibetan Plateau (TP) heat flux, the TP monsoon is closely connected with the global climate, especially pertaining to the TP. However, the current research focuses more on the influence of the TP monsoon on the TP and eastern China, but not including Central Asia. This paper analyzed the relationship between the TP monsoon index and Central Asia summer precipitation by JRA55 reanalysis data and Global Precipitation Climatology Centre (GPCC) monthly precipitation. The results showed a significant positive relationship between the TP monsoon index and summer precipitation in Central Asia. When the TP monsoon was strong, there was cold advection in the upper troposphere over Central Asia, and the resulting thermal wind caused a cyclonic circulation anomaly in the mid-upper troposphere over Central Asia. This in turn led to a cyclonic circulation anomaly to water vapor transport in the lower troposphere. The abnormal upward movement also caused more precipitation in this area, which explains the positive correlation between the TP monsoon and the precipitation in Central Asia. Based on this physical mechanism, the temperature of the mid-upper troposphere over Central Asia was closely related to the TP monsoon, and it was a key factor that affected summer precipitation changes in Central Asia.